Population Genetic Diversity and Clustering Analysis for Chinese Dongxiang Group With 30 Autosomal InDel Loci Simultaneously Analyzed - Zhu, Bofeng; Lan, Qiong; Guo, Yuxin; Xie, Tong; Fang, Yating; Jin, Xiaoye; Cui, Wei; Chen, Chong; Zhou, Yongsong; Li, Xiaogang (Frontiers in Genetics, 2018)
In comparison with the most preferred genetic marker utilized in forensic science (STR), insertion/deletion analysis possesses further benefits, like absence of stutter peak, low mutation rate and enabling mixed stain analysis. At present, a total of 169 unrelated healthy Dongxiang individuals dwelling in Dongxiang Autonomous county of Gansu province were recruited in our study to appraise the forensic usefulness of the panel including 30 autosomal diallelic genetic markers. The insertion allele frequencies were in the range of 0.1598 at HLD 111 to 0.8850 at HLD 118. The cumulative match of probability and the combined probability of exclusion were estimated based on independence of pairwise loci, with the values of 3.96×10-11 and 0.9886, respectively, which showed tremendous potential of this panel to be qualified for forensic personal identification in Chinese Dongxiang group. And also, it could also be used as a complementary tool instrument for forensic parentage testing when combined with standard STR genetic markers. Furthermore, calculation of the DA distance and Fst values of pairwise populations, phylogenetic reconstructions, multidimensional scaling analysis, structure clustering analysis were also conducted to probe the genetic relationships between Dongxiang group and the other 30 reference populations. Results demonstrated that Dongxiang ethnic group might be genetically closer related with most Chinese populations involved in our study, especially Tibet groups, Xibe group and several Han populations. Keywords: InDel, polymorphism analysis, Dongxiang, population genetics, clustering analysis